2005
DOI: 10.1007/s00428-005-0120-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of claudin-2 in normal human tissues and gastrointestinal carcinomas

Abstract: Claudins are involved in the formation of tight junctions in epithelial and endothelial cells. Claudins form a family of 24 members displaying organ- and tissue-specific patterns of expression. In the present study, we evaluated the specificity of the claudin-2 expression in various normal human tissues and gastrointestinal cancers by quantitative reverse transcriptase-polymerase chain reaction and immunohistochemistry. In 14 various normal tissues, claudin-2 mRNA was expressed in the kidney, liver, pancreas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 22 publications
1
47
0
2
Order By: Relevance
“…In our sample set, we found weak or moderate claudin-2 positivity in liver metastases of colorectal and pancreatic cancers. Obvious claudin-2 expression has already been described in 25.3% of colorectal (Aung et al 2006) and 45% of pancreatic adenocarcinomas (Borka et al 2007). Thus, claudin-2 may not only participate in the carcinogenesis of these tumors but may also contribute to a metastatic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In our sample set, we found weak or moderate claudin-2 positivity in liver metastases of colorectal and pancreatic cancers. Obvious claudin-2 expression has already been described in 25.3% of colorectal (Aung et al 2006) and 45% of pancreatic adenocarcinomas (Borka et al 2007). Thus, claudin-2 may not only participate in the carcinogenesis of these tumors but may also contribute to a metastatic phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, claudin-2 has been observed for gastric carcinomas and colorectal cancer, which are both highly metastatic to the liver (1,15,21). It is conceivable that claudin-2 expression is selected for in primary liver cancer and in solid cancer cells that display a propensity to metastasize to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Altered expression of claudins has been reported in several malignant tumors, including those of the ovary [22,35,36] , prostate [23] , breast [24,37] , pancreas [25] , colorectum [26,38] and stomach [39] in comparison with the corresponding normal tissues; however, little is known about the mechanism through which claudins control cancer cell behavior. A previous study reported that 75% of the stage II CRCs exhibited elevated levels of claudin-1 expression, while decreased claudin-1 expression was directly associated with higher tumor grade, recurrence and poor survival [26] .…”
Section: Discussionmentioning
confidence: 99%